Penerapan Web-Based Portfolio Dalam Pembelajaran Pendidikan Agama Islam (PAI); Sebuah Ilustrasi - Rahman, Moh. Rifqi; Mu’asholi, Maya Eka Armita (JOIES (Journal of Islamic Education Studies), 2022)
Technology is developing so rapidly. In everyday life, technology seems to never be separated from all human activities, including in educational activities, especially the learning process. Technology along with its development always provides a varied touch to the learning process, and one of the technological developments that provides variation in the learning process is the emergence of web-based portfolios which are based on the concept of the portfolio itself. In simple terms, a portfolio can be described as a collection of student work in the form of hardcopy documents, through which the teacher can then see the progress of students from time to time. Based on this, this study will review what is a web-based portfolio, basic understanding, how far is it useful in the world of special education learning, as well as an overview of its application in learning, especially learning Islamic religious education (PAI), and what are the advantages when applied.